SYNERGY OF DIGITAL TRANSFORMATION AND THE GREEN TRANSITION AS A DRIVER OF EU COMPETITIVENESS: LESSONS FOR UKRAINE - Тараненко, Ірина; Мостова, Анастасія; Мішустіна, Тетяна; Стрельченко, Інна (SWorldJournal, 2025)
This article explores the synergy between digital transformation and the green transition as a driver of EU economic competitiveness and draws lessons for Ukraine. The EU’s “twin transition” integrates digital technologies—such as AI, smart grids, digital